Effect of rapid thermal annealing time on Au/SiOx film prepared by hot wire assisted plasma enhanced chemical vapour deposition technique - Chan, K.W.; Aspanut, Zarina; Rahman, S.A. (Elsevier, 2013)
In this study, nanocomposite material consisting of silicon suboxide (SiOx ) film embedded with gold nanoparticles (Au NPs) was synthesized using hybrid technique combining hot wire evaporation and plasma enhanced chemical vapour deposition (PECVD) method. As prepared Au/SiOx films were rapid thermal annealed at constant temperature of 800 °C for different annealing times from 30 to 120 s. The use of tungsten filament for Au evaporation allowed the effective reduction of the silicon content. Depth profiling analysis confirmed the embedded in structure of Au/SiOx film. FESEM, UV/VIS/NIR and PL spectroscopy were utilized to study the structural and optical properties of annealed Au/SiOx film for different times. Embedded Au NPs diffused towards the surface of SiOx film agglomerate and increased in size with an increase in annealing time. Localized surface plasmon resonance (LSPR) peak induced by Au NPs in SiOx, which is dependent on annealing time, was clearly observed in optical spectra. Intensity and position of the PL peak located at 580 nm experienced a decrease and red-shift, as annealing time increased. © 2013 Elsevier B.V. All rights reserved.